WT1 Peptide Cancer Vaccine for Patients with Hematopoietic Malignancies and Solid Cancers - Yoshihiro Oka; Akihiro Tsuboi; Olga A. Elisseeva; Hiroko Nakajima; Fumihiro Fujiki; Manabu Kawakami; Toshiaki Shirakata; Sumiyuki Nishida; Naoki Hosen; Yusuke Oji; Ichiro Kawase; Haruo Sugiyama (The Scientific World Journal)
Wild-type Wilms' tumor gene WT1 is expressed at a high level in hematopoietic malignancies including acute leukemia, chronic myelogenous leukemia, and myelodysplastic syndromes, as well as in various kinds of solid cancers. Human cytotoxic T lymphocytes (CTLs), which could specifically lyse WT1-expressing tumor cells with HLA class I restriction, were generated in vitro. It was also demonstrated that mice immunized with the WT1 peptide rejected challenges by WT1-expressing cancer cells and survived with no signs of autoaggression to normal organs that physiologically expressed WT1. Furthermore, we and others detected IgM and IgG WT1 antibodies in patients with hematopoietic malignancies, indicating that the WT1 protein was highly immunogenic, and that immunoglobulin class-switch-inducing, WT1-specific, cellular immune responses were elicited in these patients. CD8+ WT1-specific CTLs were also detected in peripheral blood or tumor-draining lymph nodes of cancer patients. These results provided us with the rationale for elicitation of CTL responses targeting the WT1 product for cancer immunotherapy. On the basis of these findings, we performed a phase I clinical trial of a WT1 peptide cancer vaccine for the patients with malignant neoplasms. These results strongly suggested that the WT1 peptide cancer vaccine had efficacy in the clinical setting because clinical responses, including reduction of leukemic blast cells or regression of tumor masses, were observed after the WT1 vaccination in patients with hematopoietic malignancies or solid cancers. The power of a tumor-associated-antigen (TAA)-derived cancer vaccine may be enhanced in combination with stronger adjuvants, helper peptide, molecular-target-based drugs, or some chemotherapy drugs, such as gemcitabine, which has been revealed to suppress regulartory T-cell function. In contrast, reduction of WT1 peptide dose may be needed for the treatment of patients with hematological stem cell diseases, because rapid and strong destruction of malignant cell-sustained hematopoiesis before recovery of normal hematopoiesis may lead to pancytopenia in these patients.